Menakar Cokroaminoto dalam Deretan Mufasir Nusantara - M. Wiyono (AL-TAHRIR, 2017)
Abstrack: Tjokroaminoto is a National hero and one of the pioneers of Indonesia’s independence. He was born and raised in a religious family which, to some extent, has influenced his thought and political views and activities. One of the most prominent ideas of Tjokroaminoto is the concept of Islamic socialism that has been well illustrated in his monumental book entitled ‘Islam dan Socialism’. The book is a response of Tjokroaminoto toward Karl Marx’s socialism in the west and Pan-Islamism in Turkey. Tjokroaminoto, in his book, significantly cites Quranic verses and hadith as the argumentative foundation of Islamic socialism, particularly on the concept of equality, brotherhood, and discussion for convention (musyawarah) as the main value of democracy. Due to the significant amount of Quranic verses cited by Tjokroaminoto, one of Islamic universities in Jakarta classify ‘Islam and Socialism’ as an exegesis book in the region of Nusantara. This means that the author is a Mufassir (the writer of a commentary on Quran). However, this assumption needs a further research and investigation in order to assure that the work of Tjokroaminoto can be counted as Quranic exegesis book. The investigation may include testing the work toward the valid criteria of authentic and reliable Quranic exegesis work, in terms of its method, type, and other significant features..الملخص :كان جوكروامينوتو هو الرائد إبطال تحريرة جمهورية الاندونيسيا ، ولد ونشئ في بيئة أسرية دينية حتى تؤثر على أفكاره فى فعلية السياسية والأنشطة. إحداها من مؤلفته عن مفهوم الاشتراكية الإسلامية التى تصب في الرسالة المشهورة بعنوان “Islam dan Sosialisme” هذا الكتاب يتضمن استجابة جوكروامينوتو على الاشتراكية كارل ماركس (Karl Marx) التي عامت في الغربية والحركة الإسلامية (Pan-Islamisme ) في تركيا في وقت واحد. و نقل جوكروامينوتو في مؤلفته كثيرة من آيات القرآن والسنة فى حجته, خاصة فى الحوار المساواة والأخوة والمشاورة فى ممارسة الديمقراطية. ولأجل عدد كثير من الآيات التي نقلت في ذالك الكتاب كان إحدى كلية دراسة العليا بجاكرتا، والإسلام والاشتراكية يدخل في تأليف تفسير الإندونيسي (Tafsir Nusantara) إن كان هذا الكتاب يعد من كتب التفسير فالمؤلفه يسمى المفسر . لتحصيل إلى هذا المفهوم يحتج إلى التحقيق العلمية للتأكدة بأنه من كتب التفسير .  وفقا نظرية كتاب التفسير من طريقته و منهجه و لونه ووشروط المفسر التي يجب إستوفيهاAbstrak: Tjokroaminoto adalah konseptor sekaligus pahlawan perintis kemerdekaan republik Indonesia, ia lahir dan dibesarkan di dalam lingkungan keluarga yang sangat religius sehingga mempengaruhi pemikiran dan aktifitas politiknya. Salah satunya adalah konsep sosialisme Islam yang ia tuangkan dalam sebuah karya monumental berjudul ‘Islam dan Socialisme’. Buku tersebut merupakan respon Tjokroaminoto terhadap sosialisme Karl Marx yang berkembang di Barat, bersamaan dengan sosialisme tersebut, berkembang pula Pan-Islamisme di Turki pada masa itu. Tjokroaminoto di dalam bukunya tersebut banyak mengutip ayat-ayat al Qur'an dan Sunnah sebagai papan bantalan argumentasi sosialisme Islam, terutama dalam konsep persamaan, persaudaraan dan musyawarah sebagai praktik demokrasi. Banyaknya ayat-ayat yang dikutip tersebut sehingga di salah satu perguruan tinggi negeri di Jakarta, Islam dan Sosialisme dimasukkan dalam deretan karya ‘tafsir nusantara’ yang berarti pengarangya adalah seorang mufasir. Perlu interogasi ilmiah lebih jauh untuk memastikan apakah karya tersebut sesuai dengan teori kitab tafsir dikaji dari perspektif metode, corak dan syarat-syarat yang harus dipenuhi oleh mufasir.